Real‐world genomic testing and treatment patterns of newly diagnosed adult acute myeloid leukemia patients within a comprehensive health system - John C. Byrd; Jennifer L. Gatz; Cynthia Lim Louis; Alice S. Mims; Uma Borate; Ashley O. Yocum; Theophilus J. Gana; Amy Burd (Cancer Medicine, 2023)
Abstract Background We evaluated the frequency of genomic testing and treatment patterns by age category in patients with newly diagnosed (ND) acute myeloid leukemia (AML) treated in both academic‐ and community‐based health systems within a single Midwestern State. Methods Retrospective analysis of data from the Indiana University Health System Enterprise Data Warehouse and two local cancer registries, of 629 patients aged ≥18 years with ND AML during 2011–2018. Primary outcome variables were, proportion of patients with genomic analysis and frequency of mutations. Chemotherapy was categorized as “standard induction” or “other chemotherapy”/targeted therapy, and hypomethylating agents. Results Overall, 13% of ND AML patients between 2011 and 2018 had evidence of a genomic sequencing report with a demonstrated increase to 37% since 2016. Genomic testing was more likely performed in patients: aged ≤60 years than >60 years (45% vs. 30%; p = 0.03), treated in academic versus community hospitals (44% vs. 26%; p = 0.01), and in chemotherapy recipients than non‐therapy recipients (46% vs. 19%; p < 0.001). Most common mutations were ASXL1, NPM1, and FLT3. Patients ≥75 years had highest proportion (46%) of multiple (≥3) mutations. Overall, 31.2% of patients with AML did not receive any therapy for their disease. This subgroup was older than chemotherapy recipients (mean age: 71.4 vs. 55.7 years, p < 0.001), and was highest (66.2%) in patients ≥75 years. Conclusions Our results highlight the unmet medical need to increase access to genomic testing to afford treatment options, particularly to older AML patients in the real‐world setting, in this new era of targeted therapies.